The Lgr5 intestinal stem cell signature: robust expression of proposed quiescent '+4' cell markers. - Muñoz, J; Stange, D; Schepers, A; van de Wetering, M; Koo, B; Itzkovitz, S; Volckmann, R; Kung, K; Koster, J; Radulescu, S; Myant, K; Versteeg, R; et al. (2012)
Two types of stem cells are currently defined in small intestinal crypts: cycling crypt base columnar (CBC) cells and quiescent '+4' cells. Here, we combine transcriptomics with proteomics to define a definitive molecular signature for Lgr5(+) CBC cells. Transcriptional profiling of FACS-sorted Lgr5(+) stem cells and their daughters using two microarray platforms revealed an mRNA stem cell signature of 384 unique genes. Quantitative mass spectrometry on the same cell populations identified 278 proteins enriched in intestinal stem cells. The mRNA and protein data sets showed a high level of correlation and a combined signature of 510 stem cell-enriched genes was defined. Spatial expression patterns were further characterized by mRNA in-situ hybridization, revealing that approximately half of the genes were expressed in a gradient with highest levels at the crypt bottom, while the other half was expressed uniquely in Lgr5(+)stem cells. Lineage tracing using a newly established knock-in mouse for one of the signature genes, Smoc2, confirmed its stem cell specificity. Using this resource, we find-and confirm by independent approaches-that the proposed quiescent/'+4' stem cell markers Bmi1, Tert, Hopx and Lrig1 are robustly expressed in CBC cells.